2014
DOI: 10.1190/geo2013-0462.1
|View full text |Cite
|
Sign up to set email alerts
|

The role of attenuation in 2D full-waveform inversion of shallow-seismic body and Rayleigh waves

Abstract: Full-waveform inversion (FWI) of Rayleigh waves is attractive for shallow geotechnical investigations due to the high sensitivity of Rayleigh waves to the S-wave velocity structure of the subsurface. In shallow-seismic field data, the effects of anelastic damping are significant. Dissipation results in a low-pass effect as well as frequency-dependent decay with offset. We found this by comparing recorded waveforms with elastic and viscoelastic wave simulation. The effects of anelastic damping must be considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 44 publications
3
61
0
Order By: Relevance
“…by (Groos et al, 2014). They concluded that the estimation of a priori quality factors is critical for inverting seismic waves in the near-surface zone .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…by (Groos et al, 2014). They concluded that the estimation of a priori quality factors is critical for inverting seismic waves in the near-surface zone .…”
Section: Introductionmentioning
confidence: 99%
“…Inverting surface waves for the S-wave velocity model fall into two categories: 1) the classical method of inverting dispersion curves (Evison et al, 1959;Park et al, 1998;Xia et al, 2004) for a 1D layered medium, and 2) waveform inversion (Groos et al, 2014;Solano et al, 2014;Dou and Ajo-Franklin, 2014) for 2D and 3D media. The classical method accurately inverts for a 1D S-wave velocity model, but becomes less accurate with increasing lateral heterogeneity in the subsurface velocity model.…”
Section: Introductionmentioning
confidence: 99%
“…We distribute them along the model surface with an equidistant spacing of 1 m. We place each receiver one grid point below the free surface to ensure an accurate amplitude scaling (Groos, 2013). In case of the P-SV simulations the receivers record the vertical, z , velocity component and in case of the SH simulations they record the horizontal crossline, , velocity component.…”
Section: Acquisition Geometrymentioning
confidence: 99%
“…The location of the test site is on a glider air eld in Rheinstetten near Karlsruhe (Germany). We obtain the subsurface model for this location from previous Rayleigh wave FWI studies (Groos, 2013;Groos et al, 2014;Binnig, 2015). Their inversion results suggest a predominantly depth dependent 1-D background model, which is superimposed by a shallow small-scale low-velocity trench.…”
Section: True and Initial Modelsmentioning
confidence: 99%
See 1 more Smart Citation